Sistem Informasi Penyebaran Penyakit Demam Berdarah Menggunakan Metode Jaringan Syaraf Tiruan Backpropagation - Supriyadi, Didi; Adi, Kusworo; Sarwoko, Eko Adi (Universitas Diponegoro, 2011)
Dengue disease is a major health problem and endemic in several countries including Indonesia. Indonesia is included in the category